Prediction of frequency-dependent attenuation of blast-induced vibration in underground excavation. Issue 12 (15th October 2021) - Zhou, J. R.; Lu, W. B.; Zhong, D. W.; Leng, Z. D.; Wu, L.; Yan, P.
Abstract: Frequency-based criteria for control of blasting vibrations require methods to predict both peak particle velocity and dominant frequency. In this study, based on the theory of dynamics of structures a mechanical model is built firstly to derive vibration response to a cylindrical explosion source. According to model analysis, a theoretical formula is proposed to predict the frequency-dependent attenuation of vibration induced by cylindrical explosion source. With the application of dimensional analysis, a mathematical relationship is established between the dominant frequency and its principal influencing factors. The prediction formulae derived from model analysis, and dimensional analysis showed completely consistency in the formula form, indicated that the formula obeys both the method of dynamics of structures and the dimensional homogeneity. In the end the applicability of the proposed formula is verified by single-hole blasting experiments. The prediction accuracy of the proposed formula is compared with some other prediction formulae and the new proposed formula proved to be superior with a higher fitting degree and lower deviation. In addition, application of the prediction method in multi-hole blasting is discussed. With a simplified equation to predict dominant vibration frequency, the research would give a significant guiding path for future blasting engineering.